Regional Implications of the Arab Spring - Tarnawski, Marcin (Przegląd Strategiczny, 2013)
2012 revolutions in the Arab world sparked strong worldwide interest, mainly due to the easiness with which long-reigning dictators were renouncing their power. However, the shift of power did not make those who led to overthrowing the tyrants any better off. As the price of freedom seems incalculable, it is difficult to assess unequivocally all the costs of the so-called Arab revolutions: the number of people killed and displaced, changes to the size of economies and the standard of living, the impact on both the nearest neighbours and the situation in the region. The purpose of this article is to present the international implications of the Arab Spring. Detailed analysis will focus on the regional context, because the most important changes took place in the the nearest neighbours of these countries. Firstly, the Arab Spring toppled some myths about the changes in the region. Secondly, a change of government that took place in the Libya and Egypt, scared the other leaders in the region. As a result, the rulers undertook measures aimed at reducing social tensions (budget transfers for the poorest). Thirdly, the intervention in Libya showed that the West can intervene militarily in its nearest surroundings, when its interests are threatened.